Cautious communicators: Strategic communication of European Union commissioners in regulatory decision-making. (September 2022) - Müller, Moritz; Braun, Caelesta; Fraussen, Bert
The bureaucratic reputation literature stipulates that bureaucracies strategically aim to maximize reputational benefits and minimize reputational damages through targeted communication strategies. Departing from this assumption and using an extensive dataset on the media coverage of 54 legislative acts, we examine the conditions under which commissioners appear in the news and which communication strategies they pursue. Our analyses show that commissioners are more likely to appear in news coverage in the context of technically complex issues. We find that if a regulation is less politically conflictual, they are more likely to promote the commission's policy preferences, whereas they adopt a more passive style of communication in the face of political conflict. The findings further our understanding of regulatory policymaking by explaining bureaucratic behaviour through a communicational lens.